Characteristics and Clinical Outcomes of COVID-19 in ESRD Patients Undergoing Hemodialysis in Ngudi Waluyo Wlingi General Hospital in 2020-2022 - Fajar Hadi Wijayanto; Aleyda Zahratunany Insanitaqwa; Syarifiyana Mawaddah (Indonesian Journal of Kidney and Hypertension, 2024)
Background: The coronavirus disease (COVID-19) pandemic is a major threat to global health care. Comorbidities, including end-stage renal disease (ESRD), are related to an increased risk of severe infection and mortality. Objective: To assess determinants related to the clinical outcomes of COVID-19 in ESRD patients undergoing hemodialysis in Ngudi Waluyo Wlingi General Hospital in 2020-2022. Methods: This study included ESRD patients undergoing maintenance hemodialysis who were hospitalized at Ngudi Waluyo Wlingi General Hospital due to COVID-19 from May 2020 to February 2022. Clinical characteristics were investigated in relation to the severity and survival status. Results: A total of 26 patients (46.15% male) with a mean age of 52.27±13.65 years met the inclusion criteria. Of these, 42.3% had a mild infection, 23% had a moderate infection, 30.77% had a severe infection, and 3.8% had a critical infection. The mortality rate was 23.08%, with a mean length of stay of 15.19±7 days. Age, oxygen saturation, respiratory rate upon admission, lymphocyte and neutrophil levels, and neutrophil-to-lymphocyte ratio were significantly associated with COVID-19 severity. Length of stay was statistically influenced by respiratory rate upon admission. The mortality rate was correlated with the dialysis vintage, levels of hemoglobin, leukocytes, platelets, neutrophils, neutrophil-to-lymphocyte ratio, serum urea, serum creatinine, eGFR, and length of stay. Conclusion: COVID-19 in ESRD patients undergoing hemodialysis were more likely to have a poor prognosis. Identifying determinants is crucial for reducing morbidity and mortality.